2020
DOI: 10.1186/s13578-020-00467-3
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and its role in regeneration and remodeling within invertebrate

Abstract: Background Acting as a cellular cleaner by packaging and transporting defective proteins and organelles to lysosomes for breakdown, autophagic process is involved in the regulation of cell remodeling after cell damage or cell death in both vertebrate and invertebrate. In human, limitations on the regenerative capacity of specific tissues and organs make it difficult to recover from diseases. Comprehensive understanding on its mechanism within invertebrate have strong potential provide helpful information for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 159 publications
(106 reference statements)
0
8
0
Order By: Relevance
“…Initially, in yeast, cells only used the autophagy program to fulfill autologous metabolic needs or renew certain organelles, thereby maintaining the vitality of cells suffering from nutritional deterioration [ 53 ]. However, in higher eukaryotes, autophagy plays much more complicated and multifunctional roles in regulating cell survival and death, especially in cancer cells [ 27 , 29 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Initially, in yeast, cells only used the autophagy program to fulfill autologous metabolic needs or renew certain organelles, thereby maintaining the vitality of cells suffering from nutritional deterioration [ 53 ]. However, in higher eukaryotes, autophagy plays much more complicated and multifunctional roles in regulating cell survival and death, especially in cancer cells [ 27 , 29 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy signal transduction is mainly regulated by Atgs, including Atg‐3, ‐4, ‐5, ‐7, ‐10, ‐12, ‐13, ‐14, and ‐16, which underlies the mechanisms of autophagosome formation. Atgs promotes the formation of autophagosomes by regulating the light chain 3 (LC3)‐II complex (Song et al, 2020). Besides, the complex process of autophagy is involved diverse crucial signaling pathway.…”
Section: Insights Into Rcds In Gcmentioning
confidence: 99%
“…They show a relatively smooth surface with several pores and can be found as encrusting species growing over coral rubbles [29]. In 2013, Yamazaki et al [30] reported the cytotoxic activity of the pentacyclic alkaloid papuamine (1S,2E,4E,6S,7R,12S,14R,20R,22S,27R)-15,19diazapentacyclo[18.7.0.0 6,14 .0 7,12 .0 22,27 ]heptacosa-2,4-diene, Figure 1), the major constituent of these sponges, in MCF-7 breast cancer cells.…”
Section: Autophagy Modulators From Poriferamentioning
confidence: 99%
“…It is well-known that invertebrates are endowed with a remarkable ability to regenerate tissue and organs, and that the efficiency of this process is guaranteed by an appropriate regulation of autophagy. In addition, autophagy is a survival mechanism allowing aquatic organisms to withstand different stress conditions, such as hyperthermia and exposure to toxic compounds [26,27]. By considering the things mentioned, the aim of this review is to pick up selected studies that report the extraction and identification of marine animal-derived mixed fractions or isolated compounds which exert a modulatory effect on the autophagic process in breast cancer cells and list them with respect to the taxonomical hierarchy of the producing species.…”
Section: Autophagy Modulators From Poriferamentioning
confidence: 99%
See 1 more Smart Citation